Intermittent left bundle branch block: What is the mechanism?. (5th April 2019) - Upadhyay, Gaurav A.; Tung, Roderick
Abstract: We present an illustrative case of a patient with intermittent left bundle branch block (LBBB) that underwent electrophysiological study with detailed multielectrode recordings of the right and left septum. The case elucidates the nature and location of conduction block and provides further insight into the underlying mechanisms of LBBB.